The book of queens : legendary leaders, fierce females, and wonder women who ruled the world - Drimmer, Stephanie Warren (National geographic kids., 2019)
Presents an illustrated exploration of the lives of over 100 famous and influential women from throughout history who might be called "queens," whether or not they ever sat on a throne and ruled a nation--including revolutionary rebels, groundbreaking athletes, scientists, artists, CEOs, presidents, and prime ministers. Many were or are virtuous, but many also let their power go to their heads.